Spanish visual dictionary - Lucas, Ana Cristina Llompart; Reid, Lauren (Collins, 2019)
Immerse yourself in this photographic guide to the key words and phrases in Spanish. This attractive pocket-sized is a perfect travel companion and provides a practical guide to Spanish language and culture.